4-x/3=x

Simple and best practice solution for 4-x/3=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-x/3=x equation:


x in (-oo:+oo)

4-(x/3) = x // - x

4-(x/3)-x = 0

4-4/3*x = 0 // - 4

-4/3*x = -4 // : -4/3

x = -4/(-4/3)

x = 3

x = 3

See similar equations:

| 8x^5(-4x^6-9)= | | y/3-y/4=5 | | 2x+9-9=61-9 | | 2x+9-9=61 | | 3senx=-4cosx | | 2x+5-3(x-5)=1 | | 1/7000 | | 2x+7-7=67 | | y=16x+8 | | 6x-5/4=x | | 0.3x+x=130 | | 0.7x+x=255 | | 3x^2+14x-104=0 | | -11+2x=9-3x | | 6+2x=14-3x | | x-5/3-1=3 | | (-6x-3)+(3x-2)=-11 | | (b+11)(b-11)= | | 4y+6=54 | | 5x^2+4xy-y^2=0 | | x^2-30x+1=0 | | 2x-3y=44 | | 3x^2+2x=4-7x | | x^2+4mx+8-4m=0 | | (12x^2)= | | 4m^2=24 | | y^(1/4) | | x^2-300x-30000=0 | | -1/3(3w-15)=-1/5(25-5w) | | 20p/3=40*3 | | (2y+1)(y-3)-3y(y+2)=y(2-y)+10 | | 2n-1=5n |

Equations solver categories